If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + -3) = 5 + -3z Reorder the terms: 4(-3 + z) = 5 + -3z (-3 * 4 + z * 4) = 5 + -3z (-12 + 4z) = 5 + -3z Solving -12 + 4z = 5 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. -12 + 4z + 3z = 5 + -3z + 3z Combine like terms: 4z + 3z = 7z -12 + 7z = 5 + -3z + 3z Combine like terms: -3z + 3z = 0 -12 + 7z = 5 + 0 -12 + 7z = 5 Add '12' to each side of the equation. -12 + 12 + 7z = 5 + 12 Combine like terms: -12 + 12 = 0 0 + 7z = 5 + 12 7z = 5 + 12 Combine like terms: 5 + 12 = 17 7z = 17 Divide each side by '7'. z = 2.428571429 Simplifying z = 2.428571429
| (7(1/3y))-4=10 | | (M)(10)=n | | 5x-10(x-2)=x^2 | | 3ab^2-6b= | | 15x=7x-(11-4x) | | 0.75x=24 | | X^72/8x4 | | 2p/3p | | 8.1a+2.3=5.1-3.1 | | 5b-5=7b | | y=-(x+9)2-15 | | 5(x+7)=10x+20 | | C=320+5+3 | | 50=2(2x-5) | | 1898-160= | | 2x-2(x+3)=-6 | | 1898-120= | | 4a+27=9a+8 | | (X+5)(x-5)=90 | | 3/5x-y=52 | | 17=x-2 | | 30b+30m=16b+44m | | -3-3=6 | | 4-1+2x+2x-3=5x+4 | | 12n-6=4n-10 | | 217=81-v | | 3x-cos(6x)=0 | | 535+.21x=585+.13x | | (2D/7)*T=D/2-(D/4)*T | | 13x^2+8x-399=0 | | y=2x^2-6x+11 | | 0.04x^2+8.3x+4.3=0 |